Chemical approaches to discover the full potential of peptide nucleic acids in biomedical applications - Brodyagin, Nikita; Katkevics, Martins; Kotikam, Venubabu; Ryan, Christopher A.; Rozners, Eriks (Beilstein Journal of Organic Chemistry, 2021)
Peptide nucleic acid (PNA) is arguably one of the most successful DNA mimics, despite a most dramatic departure from the native structure of DNA. The present review summarizes 30 years of research on PNA’s chemistry, optimization of structure and function, applications as probes and diagnostics, and attempts to develop new PNA therapeutics. The discussion starts with a brief review of PNA’s binding modes and structural features, followed by the most impactful chemical modifications, PNA enabled assays and diagnostics, and discussion of the current state of development of PNA therapeutics. While many modifications have improved on PNA’s binding affinity and specificity, solubility and other biophysical properties, the original PNA is still most frequently used in diagnostic and other in vitro applications. Development of therapeutics and other in vivo applications of PNA has notably lagged behind and is still limited by insufficient bioavailability and difficulties with tissue specific delivery. Relatively high doses are required to overcome poor cellular uptake and endosomal entrapment, which increases the risk of toxicity. These limitations remain unsolved problems waiting for innovative chemistry and biology to unlock the full potential of PNA in biomedical applications.
Keywords: antisense; chemical modifications; diagnostics; peptide nucleic acid; PNA

(untitled) - Nielsen, P. E.; Egholm, M.; Berg, R. H.; Buchardt, O. (Science, 1991)

(untitled) - Buchardt, O.; Egholm, M.; Berg, R. H.; Nielsen, P. E. (Trends Biotechnol., 1993)

(untitled) - Nielsen, P. E.; Egholm, M.; Buchardt, O. (Bioconjugate Chem., 1994)

(untitled) - Saarbach, J.; Sabale, P. M.; Winssinger, N. (Curr. Opin. Chem. Biol., 2019)

(untitled) - Corradini, R.; Sforza, S.; Tedeschi, T.; Totsingan, F.; Marchelli, R. (Curr. Top. Med. Chem., 2007)

(untitled) - Gupta, A.; Mishra, A.; Puri, N. (J. Biotechnol., 2017)

(untitled) - Fouz, M. F.; Appella, D. H. (Molecules, 2020)

(untitled) - Frickmann, H.; Zautner, A. E.; Moter, A.; Kikhney, J.; Hagen, R. M.; Stender, H.; Poppert, S. (Crit. Rev. Microbiol., 2017)

(untitled) - Cadoni, E.; Manicardi, A.; Madder, A. (Molecules, 2020)

(untitled) - Shen, X.; Corey, D. R. (Nucleic Acids Res., 2018)

(untitled) - Setten, R. L.; Rossi, J. J.; Han, S.-p. (Nat. Rev. Drug Discovery, 2019)

(untitled) - Noble, S. A.; Bonham, M. A.; Bisi, J. E.; Bruckenstein, D. A.; Brown, P. H.; Brown, S. C.; Cadilla, R.; Gaul, M. D.; Hanvey, J. C.; Fred Hassman, C.; Josey, J. A.; Luzzio, M. J.; et al. (Drug Dev. Res., 1995)

Advances in Genetics - Lundin, K. E.; Good, L.; Strömberg, R.; Gräslund, A.; Smith, C. I. E. (Biological Activity and Biotechnological Aspects of Peptide Nucleic Acid, 2006)

(untitled) - Roberts, T. C.; Langer, R.; Wood, M. J. A. (Nat. Rev. Drug Discovery, 2020)

(untitled) - Nielsen, P. E. (Curr. Opin. Mol. Ther., 2010)

(untitled) - Nielsen, P. E. (Q. Rev. Biophys., 2005)

(untitled) - McMahon, B. M.; Mays, D.; Lipsky, J.; Stewart, J. A.; Fauq, A.; Richelson, E. (Antisense Nucleic Acid Drug Dev., 2002)

(untitled) - Egholm, M.; Buchardt, O.; Nielsen, P. E.; Berg, R. H. (J. Am. Chem. Soc., 1992)

(untitled) - Egholm, M.; Nielsen, P. E.; Buchardt, O.; Berg, R. H. (J. Am. Chem. Soc., 1992)

(untitled) - Egholm, M.; Buchardt, O.; Christensen, L.; Behrens, C.; Freier, S. M.; Driver, D. A.; Berg, R. H.; Kim, S. K.; Norden, B.; Nielsen, P. E. (Nature, 1993)

(untitled) - Wittung, P.; Nielsen, P. E.; Buchardt, O.; Egholm, M.; Nordén, B. (Nature, 1994)

(untitled) - Tomac, S.; Sarkar, M.; Ratilainen, T.; Wittung, P.; Nielsen, P. E.; Nordén, B.; Gräslund, A. (J. Am. Chem. Soc., 1996)

(untitled) - Cherny, D. Y.; Belotserkovskii, B. P.; Frank-Kamenetskii, M. D.; Egholm, M.; Buchardt, O.; Berg, R. H.; Nielsen, P. E. (Proc. Natl. Acad. Sci. U. S. A., 1993)

(untitled) - Bentin, T.; Hansen, G. I.; Nielsen, P. E. (Nucleic Acids Res., 2006)

(untitled) - Wittung, P.; Nielsen, P.; Nordén, B. (Biochemistry, 1997)

(untitled) - Hansen, M. E.; Bentin, T.; Nielsen, P. E. (Nucleic Acids Res., 2009)

(untitled) - Li, M.; Zengeya, T.; Rozners, E. (J. Am. Chem. Soc., 2010)

(untitled) - Zengeya, T.; Gupta, P.; Rozners, E. (Angew. Chem., Int. Ed., 2012)

(untitled) - Muse, O.; Zengeya, T.; Mwaura, J.; Hnedzko, D.; McGee, D. W.; Grewer, C. T.; Rozners, E. (ACS Chem. Biol., 2013)

(untitled) - Hnedzko, D.; McGee, D. W.; Karamitas, Y. A.; Rozners, E. (RNA, 2017)

(untitled) - Ryan, C. A.; Brodyagin, N.; Lok, J.; Rozners, E. (Biochemistry, 2021)

(untitled) - Doluca, O.; Withers, J. M.; Filichev, V. V. (Chem. Rev., 2013)

(untitled) - Krishnan-Ghosh, Y.; Stephens, E.; Balasubramanian, S. (J. Am. Chem. Soc., 2004)

(untitled) - Egholm, M.; Christensen, L.; Deuholm, K. L.; Buchardt, O.; Coull, J.; Nielsen, P. E. (Nucleic Acids Res., 1995)

(untitled) - Griffith, M. C.; Risen, L. M.; Greig, M. J.; Lesnik, E. A.; Sprankle, K. G.; Griffey, R. H.; Kiely, J. S.; Freier, S. M. (J. Am. Chem. Soc., 1995)

(untitled) - Kuhn, H.; Demidov, V. V.; Frank-Kamenetskii, M. D.; Nielsen, P. E. (Nucleic Acids Res., 1998)

(untitled) - Bentin, T.; Larsen, H. J.; Nielsen, P. E. (Biochemistry, 2003)

(untitled) - Hanvey, J. C.; Peffer, N. J.; Bisi, J. E.; Thomson, S. A.; Cadilla, R.; Josey, J. A.; Ricca, D. J.; Hassman, C. F.; Bonham, M. A.; Au, K. G. (Science, 1992)

(untitled) - Eriksson, M.; Nielsen, P. E. (Nat. Struct. Mol. Biol., 1996)

(untitled) - Brown, S. C.; Thomson, S. A.; Veal, J. M.; Davis, D. G. (Science, 1994)

(untitled) - Betts, L.; Josey, J. A.; Veal, J. M.; Jordan, S. R. (Science, 1995)

(untitled) - Kotikam, V.; Kennedy, S. D.; MacKay, J. A.; Rozners, E. (Chem. – Eur. J., 2019)

(untitled) - Rasmussen, H.; Kastrup, J. S.; Nielsen, J. N.; Nielsen, J. M.; Nielsen, P. E. (Nat. Struct. Mol. Biol., 1997)

(untitled) - Petersson, B.; Nielsen, B. B.; Rasmussen, H.; Larsen, I. K.; Gajhede, M.; Nielsen, P. E.; Kastrup, J. S. (J. Am. Chem. Soc., 2005)

(untitled) - He, W.; Hatcher, E.; Balaeff, A.; Beratan, D. N.; Gil, R. R.; Madrid, M.; Achim, C. (J. Am. Chem. Soc., 2008)

(untitled) - Hyrup, B.; Egholm, M.; Rolland, M.; Nielsen, P. E.; Berg, R. H.; Buchardt, O. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Hyrup, B.; Egholm, M.; Nielsen, P. E.; Wittung, P.; Norden, B.; Buchardt, O. (J. Am. Chem. Soc., 1994)

(untitled) - Kumar, V.; Brodyagin, N.; Rozners, E. (ChemBioChem, 2020)

(untitled) - Hyrup, B.; Egholm, M.; Buchardt, O.; Nielsen, P. E. (Bioorg. Med. Chem. Lett., 1996)

(untitled) - Lagriffoule, P.; Eriksson, M.; Jensen, K. K.; Nielsen, P. E.; Wittung, P.; Nordén, B.; Buchardt, O. (Chem. – Eur. J., 1997)

(untitled) - Govindaraju, T.; Gonnade, R. G.; Bhadbhade, M. M.; Kumar, V. A.; Ganesh, K. N. (Org. Lett., 2003)

(untitled) - Govindaraju, T.; Kumar, V. A.; Ganesh, K. N. (J. Org. Chem., 2004)

(untitled) - Govindaraju, T.; Kumar, V. A.; Ganesh, K. N. (J. Am. Chem. Soc., 2005)

(untitled) - Kumar, V. A.; Ganesh, K. N. (Acc. Chem. Res., 2005)

(untitled) - Myers, M. C.; Witschi, M. A.; Larionova, N. V.; Franck, J. M.; Haynes, R. D.; Hara, T.; Grajkowski, A.; Appella, D. H. (Org. Lett., 2003)

(untitled) - Pokorski, J. K.; Witschi, M. A.; Purnell, B. L.; Appella, D. H. (J. Am. Chem. Soc., 2004)

(untitled) - Govindaraju, T.; Kumar, V. A.; Ganesh, K. N. (Chem. Commun., 2004)

(untitled) - Govindaraju, T.; Kumar, V. A.; Ganesh, K. N. (J. Org. Chem., 2004)

(untitled) - Zheng, H.; Saha, M.; Appella, D. H. (Org. Lett., 2018)

(untitled) - Zheng, H.; Botos, I.; Clausse, V.; Nikolayevskiy, H.; Rastede, E. E.; Fouz, M. F.; Mazur, S. J.; Appella, D. H. (Nucleic Acids Res., 2021)

(untitled) - Vilaivan, T.; Suparpprom, C.; Harnyuttanakorn, P.; Lowe, G. (Tetrahedron Lett., 2001)

(untitled) - Mansawat, W.; Vilaivan, C.; Balázs, Á.; Aitken, D. J.; Vilaivan, T. (Org. Lett., 2012)

(untitled) - Vilaivan, T.; Lowe, G. (J. Am. Chem. Soc., 2002)

(untitled) - Vilaivan, T.; Srisuwannaket, C. (Org. Lett., 2006)

(untitled) - Vilaivan, T. (Acc. Chem. Res., 2015)

(untitled) - Muangkaew, P.; Vilaivan, T. (Bioorg. Med. Chem. Lett., 2020)

(untitled) - Nielsen, P. E.; Haaima, G.; Lohse, A.; Buchardt, O. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Püschl, A.; Sforza, S.; Haaima, G.; Dahl, O.; Nielsen, P. E. (Tetrahedron Lett., 1998)

(untitled) - Sforza, S.; Haaima, G.; Marchelli, R.; Nielsen, P. E. (Eur. J. Org. Chem., 1999)

(untitled) - Menchise, V.; De Simone, G.; Tedeschi, T.; Corradini, R.; Sforza, S.; Marchelli, R.; Capasso, D.; Saviano, M.; Pedone, C. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Zhou, P.; Wang, M.; Du, L.; Fisher, G. W.; Waggoner, A.; Ly, D. H. (J. Am. Chem. Soc., 2003)

(untitled) - Dragulescu-Andrasi, A.; Zhou, P.; He, G.; Ly, D. H. (Chem. Commun., 2005)

(untitled) - Dragulescu-Andrasi, A.; Rapireddy, S.; He, G.; Bhattacharya, B.; Hyldig-Nielsen, J. J.; Zon, G.; Ly, D. H. (J. Am. Chem. Soc., 2006)

(untitled) - Gupta, P.; Muse, O.; Rozners, E. (Biochemistry, 2012)

(untitled) - Dragulescu-Andrasi, A.; Rapireddy, S.; Frezza, B. M.; Gayathri, C.; Gil, R. R.; Ly, D. H. (J. Am. Chem. Soc., 2006)

(untitled) - He, W.; Crawford, M. J.; Rapireddy, S.; Madrid, M.; Gil, R. R.; Ly, D. H.; Achim, C. (Mol. BioSyst., 2010)

(untitled) - Yeh, J. I.; Shivachev, B.; Rapireddy, S.; Crawford, M. J.; Gil, R. R.; Du, S.; Madrid, M.; Ly, D. H. (J. Am. Chem. Soc., 2010)

(untitled) - Tähtinen, V.; Granqvist, L.; Murtola, M.; Strömberg, R.; Virta, P. (Chem. – Eur. J., 2017)

(untitled) - Englund, E. A.; Appella, D. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Englund, E. A.; Appella, D. H. (Org. Lett., 2005)

(untitled) - Sahu, B.; Chenna, V.; Lathrop, K. L.; Thomas, S. M.; Zon, G.; Livak, K. J.; Ly, D. H. (J. Org. Chem., 2009)

(untitled) - Manicardi, A.; Fabbri, E.; Tedeschi, T.; Sforza, S.; Bianchi, N.; Brognara, E.; Gambari, R.; Marchelli, R.; Corradini, R. (ChemBioChem, 2012)

(untitled) - Mitra, R.; Ganesh, K. N. (Chem. Commun., 2011)

(untitled) - Mitra, R.; Ganesh, K. N. (J. Org. Chem., 2012)

(untitled) - Kumar, P.; Jain, D. R. (Tetrahedron, 2015)

(untitled) - Tähtinen, V.; Verhassel, A.; Tuomela, J.; Virta, P. (ChemBioChem, 2019)

(untitled) - Bhingardeve, P.; Madhanagopal, B. R.; Ganesh, K. N. (J. Org. Chem., 2020)

(untitled) - Gupta, M. K.; Madhanagopal, B. R.; Ganesh, K. N. (J. Org. Chem., 2021)

(untitled) - Bahal, R.; Sahu, B.; Rapireddy, S.; Lee, C.-M.; Ly, D. H. (ChemBioChem, 2012)

(untitled) - Efimov, V. A.; Choob, M. V.; Buryakova, A. A.; Kalinkina, A. L.; Chakhmakhcheva, O. G. (Nucleic Acids Res., 1998)

(untitled) - Shiraishi, T.; Hamzavi, R.; Nielsen, P. E. (Nucleic Acids Res., 2008)

(untitled) - Avitabile, C.; Moggio, L.; Malgieri, G.; Capasso, D.; Di Gaetano, S.; Saviano, M.; Pedone, C.; Romanelli, A. (PLoS One, 2012)

(untitled) - Kirillova, Y.; Boyarskaya, N.; Dezhenkov, A.; Tankevich, M.; Prokhorov, I.; Varizhuk, A.; Eremin, S.; Esipov, D.; Smirnov, I.; Pozmogova, G. (PLoS One, 2015)

Chemical Biology No. 7: DNA-targeting Molecules as Therapeutic Agents - Fox, K. R.; Brown, T.; Rusling, D. A. (DNA Recognition by Parallel Triplex Formation, 2018)

(untitled) - Ono, A.; Ts'o, P. O. P.; Kan, L. S. (J. Am. Chem. Soc., 1991)

(untitled) - Ono, A.; Ts'o, P. O. P.; Kan, L. S. (J. Org. Chem., 1992)

(untitled) - Christensen, C.; Eldrup, A. B.; Haaima, G.; Nielsen, P. E. (Bioorg. Med. Chem. Lett., 2002)

(untitled) - Devi, G.; Yuan, Z.; Lu, Y.; Zhao, Y.; Chen, G. (Nucleic Acids Res., 2014)

(untitled) - Povsic, T. J.; Dervan, P. B. (J. Am. Chem. Soc., 1989)

(untitled) - Hildbrand, S.; Leumann, C. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Bates, P. J.; Laughton, C. A.; Jenkins, T. C.; Capaldi, D. C.; Roselt, P. D.; Reese, C. B.; Neidle, S. (Nucleic Acids Res., 1996)

(untitled) - Cassidy, S. A.; Slickers, P.; Trent, J. O.; Capaldi, D. C.; Roselt, P. D.; Reese, C. B.; Neidle, S.; Fox, K. R. (Nucleic Acids Res., 1997)

(untitled) - Krishna, M. S.; Wang, Z.; Zheng, L.; Bowry, J.; Ong, A. A. L.; Mu, Y.; Prabakaran, M.; Chen, G. (Biochemistry, 2019)

(untitled) - Eldrup, A. B.; Nielsen, B. B.; Haaima, G.; Rasmussen, H.; Kastrup, J. S.; Christensen, C.; Nielsen, P. E. (Eur. J. Org. Chem., 2001)

(untitled) - Eldrup, A. B.; Christensen, C.; Haaima, G.; Nielsen, P. E. (J. Am. Chem. Soc., 2002)

(untitled) - Patil, K. M.; Toh, D.-F. K.; Yuan, Z.; Meng, Z.; Shu, Z.; Zhang, H.; Ong, A. A. L.; Krishna, M. S.; Lu, L.; Lu, Y.; Chen, G. (Nucleic Acids Res., 2018)

(untitled) - Ong, A. A. L.; Toh, D.-F. K.; Krishna, M. S.; Patil, K. M.; Okamura, K.; Chen, G. (Biochemistry, 2019)

(untitled) - Brodyagin, N.; Maryniak, A. L.; Kumpina, I.; Talbott, J. M.; Katkevics, M.; Rozners, E.; MacKay, J. A. (Chem. – Eur. J., 2021)

(untitled) - Fox, K. R.; Brown, T. (Q. Rev. Biophys., 2005)

(untitled) - Eldrup, A. B.; Dahl, O.; Nielsen, P. E. (J. Am. Chem. Soc., 1997)

(untitled) - Ong, A. A. L.; Toh, D.-F. K.; Patil, K. M.; Meng, Z.; Yuan, Z.; Krishna, M. S.; Devi, G.; Haruehanroengra, P.; Lu, Y.; Xia, K.; Okamura, K.; Sheng, J.; et al. (Biochemistry, 2019)

(untitled) - Gupta, P.; Zengeya, T.; Rozners, E. (Chem. Commun., 2011)

(untitled) - Endoh, T.; Brodyagin, N.; Hnedzko, D.; Sugimoto, N.; Rozners, E. (ACS Chem. Biol., 2021)

(untitled) - Guianvarc’h, D.; Benhida, R.; Fourrey, J.-L.; Maurisse, R.; Sun, J.-S. (Chem. Commun., 2001)

(untitled) - Rusling, D. A.; Powers, V. E. C.; Ranasinghe, R. T.; Wang, Y.; Osborne, S. D.; Brown, T.; Fox, K. R. (Nucleic Acids Res., 2005)

(untitled) - Koshlap, K. M.; Gillespie, P.; Dervan, P. B.; Feigon, J. (J. Am. Chem. Soc., 1993)

(untitled) - Kim, K. T.; Chang, D.; Winssinger, N. (Helv. Chim. Acta, 2018)

(untitled) - Prévot-Halter, I.; Leumann, C. J. (Bioorg. Med. Chem. Lett., 1999)

(untitled) - Endoh, T.; Hnedzko, D.; Rozners, E.; Sugimoto, N. (Angew. Chem., Int. Ed., 2016)

(untitled) - Brodyagin, N.; Kumpina, I.; Applegate, J.; Katkevics, M.; Rozners, E. (ACS Chem. Biol., 2021)

(untitled) - Kumpina, I.; Brodyagin, N.; MacKay, J. A.; Kennedy, S. D.; Katkevics, M.; Rozners, E. (J. Org. Chem., 2019)

(untitled) - Toh, D.-F. K.; Devi, G.; Patil, K. M.; Qu, Q.; Maraswami, M.; Xiao, Y.; Loh, T. P.; Zhao, Y.; Chen, G. (Nucleic Acids Res., 2016)

(untitled) - Semenyuk, A.; Darian, E.; Liu, J.; Majumdar, A.; Cuenoud, B.; Miller, P. S.; MacKerell, A. D., Jr; Seidman, M. M. (Biochemistry, 2010)

(untitled) - Lin, K.-Y.; Matteucci, M. D. (J. Am. Chem. Soc., 1998)

(untitled) - Wilds, C. J.; Maier, M. A.; Tereshko, V.; Manoharan, M.; Egli, M. (Angew. Chem., Int. Ed., 2002)

(untitled) - Rajeev, K. G.; Maier, M. A.; Lesnik, E. A.; Manoharan, M. (Org. Lett., 2002)

(untitled) - Ellipilli, S.; Palvai, S.; Ganesh, K. N. (J. Org. Chem., 2016)

(untitled) - Kiviniemi, A.; Murtola, M.; Ingman, P.; Virta, P. (J. Org. Chem., 2013)

(untitled) - Haaima, G.; Hansen, H. F.; Christensen, L.; Dahl, O.; Nielsen, P. E. (Nucleic Acids Res., 1997)

(untitled) - Lohse, J.; Dahl, O.; Nielsen, P. E. (Proc. Natl. Acad. Sci. U. S. A., 1999)

(untitled) - Hudson, R. H. E.; Heidari, A.; Martin-Chan, T.; Park, G.; Wisner, J. A. (J. Org. Chem., 2019)

(untitled) - Akisawa, T.; Ishizawa, Y.; Nagatsugi, F. (Molecules, 2015)

(untitled) - Akisawa, T.; Yamada, K.; Nagatsugi, F. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Manicardi, A.; Gyssels, E.; Corradini, R.; Madder, A. (Chem. Commun., 2016)

(untitled) - Chen, D.; Meena; Sharma, S. K.; McLaughlin, L. W. (J. Am. Chem. Soc., 2004)

(untitled) - Chen, H.; Meena; McLaughlin, L. W. (J. Am. Chem. Soc., 2008)

(untitled) - Zeng, Y.; Pratumyot, Y.; Piao, X.; Bong, D. (J. Am. Chem. Soc., 2012)

(untitled) - Miao, S.; Liang, Y.; Marathe, I.; Mao, J.; DeSantis, C.; Bong, D. (J. Am. Chem. Soc., 2019)

(untitled) - Thadke, S. A.; Perera, J. D. R.; Hridya, V. M.; Bhatt, K.; Shaikh, A. Y.; Hsieh, W.-C.; Chen, M.; Gayathri, C.; Gil, R. R.; Rule, G. S.; Mukherjee, A.; Thornton, C. A.; et al. (Biochemistry, 2018)

(untitled) - Thadke, S. A.; Hridya, V. M.; Perera, J. D. R.; Gil, R. R.; Mukherjee, A.; Ly, D. H. (Commun. Chem., 2018)

(untitled) - Ward, D. C.; Reich, E.; Stryer, L. (J. Biol. Chem., 1969)

(untitled) - Gangamani, B. P.; Kumar, V. A. (Chem. Commun., 1997)

(untitled) - Hudson, R. H. E.; Viirre, R. D.; McCourt, N.; Tse, J. (Nucleosides, Nucleotides Nucleic Acids, 2003)

(untitled) - Wojciechowski, F.; Hudson, R. H. E. (J. Am. Chem. Soc., 2008)

(untitled) - Wojciechowski, F.; Hudson, R. H. E. (Org. Lett., 2009)

(untitled) - Suchý, M.; Hudson, R. H. E. (J. Org. Chem., 2014)

(untitled) - Cheruiyot, S. K.; Rozners, E. (ChemBioChem, 2016)

(untitled) - Krishna, M. S.; Toh, D.-F. K.; Meng, Z.; Ong, A. A. L.; Wang, Z.; Lu, Y.; Xia, K.; Prabakaran, M.; Chen, G. (Anal. Chem. (Washington, DC, U. S.), 2019)

(untitled) - Ishiguro, T.; Saitoh, J.; Yawata, H.; Otsuka, M.; Inoue, T.; Sugiura, Y. (Nucleic Acids Res., 1996)

(untitled) - Köhler, O.; Seitz, O. (Chem. Commun., 2003)

(untitled) - Svanvik, N.; Westman, G.; Wang, D.; Kubista, M. (Anal. Biochem., 2000)

(untitled) - Svanvik, N.; Nygren, J.; Westman, G.; Kubista, M. (J. Am. Chem. Soc., 2001)

(untitled) - Sato, T.; Sato, Y.; Nishizawa, S. (J. Am. Chem. Soc., 2016)

(untitled) - Sato, T.; Sato, Y.; Nishizawa, S. (Chem. – Eur. J., 2017)

(untitled) - Kolevzon, N.; Hashoul, D.; Naik, S.; Rubinstein, A.; Yavin, E. (Chem. Commun., 2016)

(untitled) - Koppelhus, U.; Nielsen, P. E. (Adv. Drug Delivery Rev., 2003)

(untitled) - Quijano, E.; Bahal, R.; Ricciardi, A.; Saltzman, W. M.; Glazer, P. M. (Yale J. Biol. Med., 2017)

(untitled) - Montazersaheb, S.; Hejazi, M. S.; Nozad Charoudeh, H. (Adv. Pharm. Bull., 2018)

(untitled) - Karras, J. G.; Maier, M. A.; Lu, T.; Watt, A.; Manoharan, M. (Biochemistry, 2001)

(untitled) - Siwkowski, A. M.; Malik, L.; Esau, C. C.; Maier, M. A.; Wancewicz, E. V.; Albertshofer, K.; Monia, B. P.; Bennett, C. F.; Eldrup, A. B. (Nucleic Acids Res., 2004)

Delivery Technologies for Biopharmaceuticals: Peptides, Proteins, Nucleic Acids and Vaccines - Shiraishi, T.; Nielsen, P. E. (Cellular bioavailability of peptide nucleic acids (PNAs) conjugated to cell penetrating peptides, 2009)

(untitled) - Mäe, M.; El Andaloussi, S.; Lehto, T.; Langel, Ü. (Expert Opin. Drug Delivery, 2009)

(untitled) - Shiraishi, T.; Nielsen, P. E. (Nat. Protoc., 2006)

(untitled) - Abes, S.; Turner, J. J.; Ivanova, G. D.; Owen, D.; Williams, D.; Arzumanov, A.; Clair, P.; Gait, M. J.; Lebleu, B. (Nucleic Acids Res., 2007)

(untitled) - Pardridge, W. M.; Boado, R. J.; Kang, Y. S. (Proc. Natl. Acad. Sci. U. S. A., 1995)

(untitled) - Basu, S.; Wickstrom, E. (Bioconjugate Chem., 1997)

(untitled) - Derossi, D.; Joliot, A. H.; Chassaing, G.; Prochiantz, A. (J. Biol. Chem., 1994)

(untitled) - Fawell, S.; Seery, J.; Daikh, Y.; Moore, C.; Chen, L. L.; Pepinsky, B.; Barsoum, J. (Proc. Natl. Acad. Sci. U. S. A., 1994)

(untitled) - Pooga, M.; Hällbrink, M.; Zorko, M.; Langel, Ü. (FASEB J., 1998)

(untitled) - Simmons, C. G.; Pitts, A. E.; Mayfield, L. D.; Shay, J. W.; Corey, D. R. (Bioorg. Med. Chem. Lett., 1997)

(untitled) - Pooga, M.; Soomets, U.; Hällbrink, M.; Valkna, A.; Saar, K.; Rezaei, K.; Kahl, U.; Hao, J.-X.; Xu, X.-J.; Wiesenfeld-Hallin, Z.; Hökfelt, T.; Bartfai, T.; et al. (Nat. Biotechnol., 1998)

(untitled) - Cutrona, G.; Carpaneto, E. M.; Ulivi, M.; Roncella, S.; Landt, O.; Ferrarini, M.; Boffa, L. C. (Nat. Biotechnol., 2000)

(untitled) - Braun, K.; Peschke, P.; Pipkorn, R.; Lampel, S.; Wachsmuth, M.; Waldeck, W.; Friedrich, E.; Debus, J. (J. Mol. Biol., 2002)

(untitled) - Koppelhus, U.; Awasthi, S. K.; Zachar, V.; Holst, H. U.; Ebbesen, P.; Nielsen, P. E. (Antisense Nucleic Acid Drug Dev., 2002)

(untitled) - Turner, J. J.; Ivanova, G. D.; Verbeure, B.; Williams, D.; Arzumanov, A. A.; Abes, S.; Lebleu, B.; Gait, M. J. (Nucleic Acids Res., 2005)

(untitled) - Zeng, Z.; Han, S.; Hong, W.; Lang, Y.; Li, F.; Liu, Y.; Li, Z.; Wu, Y.; Li, W.; Zhang, X.; Cao, Z. (Mol. Ther.–Nucleic Acids, 2016)

(untitled) - Hunt, J. F.; Rath, P.; Rothschild, K. J.; Engelman, D. M. (Biochemistry, 1997)

(untitled) - Andreev, O. A.; Karabadzhak, A. G.; Weerakkody, D.; Andreev, G. O.; Engelman, D. M.; Reshetnyak, Y. K. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - An, M.; Wijesinghe, D.; Andreev, O. A.; Reshetnyak, Y. K.; Engelman, D. M. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Andreev, O. A.; Engelman, D. M.; Reshetnyak, Y. K. (Front. Physiol., 2014)

(untitled) - Cheng, C. J.; Bahal, R.; Babar, I. A.; Pincus, Z.; Barrera, F.; Liu, C.; Svoronos, A.; Braddock, D. T.; Glazer, P. M.; Engelman, D. M.; Saltzman, W. M.; Slack, F. J. (Nature, 2015)

(untitled) - Kaplan, A. R.; Pham, H.; Liu, Y.; Oyaghire, S.; Bahal, R.; Engelman, D. M.; Glazer, P. M. (Mol. Cancer Res., 2020)

(untitled) - Lu, Z.; Paolella, B. R.; Truex, N. L.; Loftis, A. R.; Liao, X.; Rabideau, A. E.; Brown, M. S.; Busanovich, J.; Beroukhim, R.; Pentelute, B. L. (ACS Chem. Biol., 2020)

(untitled) - Sazani, P.; Kang, S.-H.; Maier, M. A.; Wei, C.; Dillman, J.; Summerton, J.; Manoharan, M.; Kole, R. (Nucleic Acids Res., 2001)

(untitled) - Sazani, P.; Gemignani, F.; Kang, S.-H.; Maier, M. A.; Manoharan, M.; Persmark, M.; Bortner, D.; Kole, R. (Nat. Biotechnol., 2002)

(untitled) - Hu, J.; Matsui, M.; Gagnon, K. T.; Schwartz, J. C.; Gabillet, S.; Arar, K.; Wu, J.; Bezprozvanny, I.; Corey, D. R. (Nat. Biotechnol., 2009)

(untitled) - Hu, J.; Corey, D. R. (Biochemistry, 2007)

(untitled) - Fabani, M. M.; Gait, M. J. (RNA, 2008)

(untitled) - Wancewicz, E. V.; Maier, M. A.; Siwkowski, A. M.; Albertshofer, K.; Winger, T. M.; Berdeja, A.; Gaus, H.; Vickers, T. A.; Bennett, C. F.; Monia, B. P.; Griffey, R. H.; Nulf, C. J.; et al. (J. Med. Chem., 2010)

(untitled) - Fabani, M. M.; Abreu-Goodger, C.; Williams, D.; Lyons, P. A.; Torres, A. G.; Smith, K. G. C.; Enright, A. J.; Gait, M. J.; Vigorito, E. (Nucleic Acids Res., 2010)

(untitled) - Torres, A. G.; Fabani, M. M.; Vigorito, E.; Williams, D.; Al-Obaidi, N.; Wojciechowski, F.; Hudson, R. H. E.; Seitz, O.; Gait, M. J. (Nucleic Acids Res., 2012)

(untitled) - Kaihatsu, K.; Huffman, K. E.; Corey, D. R. (Biochemistry, 2004)

(untitled) - Wright, D. G.; Zhang, Y.; Murphy, J. R. (Biochem. Biophys. Res. Commun., 2008)

(untitled) - Good, L.; Nielsen, P. E. (Proc. Natl. Acad. Sci. U. S. A., 1998)

(untitled) - Vaara, M.; Porro, M. (Antimicrob. Agents Chemother., 1996)

(untitled) - Good, L.; Awasthi, S. K.; Dryselius, R.; Larsson, O.; Nielsen, P. E. (Nat. Biotechnol., 2001)

(untitled) - Abes, S.; Moulton, H. M.; Clair, P.; Prevot, P.; Youngblood, D. S.; Wu, R. P.; Iversen, P. L.; Lebleu, B. (J. Controlled Release, 2006)

(untitled) - Ivanova, G. D.; Arzumanov, A.; Abes, R.; Yin, H.; Wood, M. J. A.; Lebleu, B.; Gait, M. J. (Nucleic Acids Res., 2008)

(untitled) - Richard, J. P.; Melikov, K.; Brooks, H.; Prevot, P.; Lebleu, B.; Chernomordik, L. V. (J. Biol. Chem., 2005)

(untitled) - Stanzl, E. G.; Trantow, B. M.; Vargas, J. R.; Wender, P. A. (Acc. Chem. Res., 2013)

(untitled) - Brognara, E.; Fabbri, E.; Bazzoli, E.; Montagner, G.; Ghimenton, C.; Eccher, A.; Cantù, C.; Manicardi, A.; Bianchi, N.; Finotti, A.; Breveglieri, G.; Borgatti, M.; et al. (J. Neuro-Oncol., 2014)

(untitled) - Qian, Z.; Martyna, A.; Hard, R. L.; Wang, J.; Appiah-Kubi, G.; Coss, C.; Phelps, M. A.; Rossman, J. S.; Pei, D. (Biochemistry, 2016)

(untitled) - Soudah, T.; Khawaled, S.; Aqeilan, R. I.; Yavin, E. (ACS Omega, 2019)

(untitled) - Muratovska, A.; Lightowlers, R. N.; Taylor, R. W.; Turnbull, D. M.; Smith, R. A. J.; Wilce, J. A.; Martin, S. W.; Murphy, M. P. (Nucleic Acids Res., 2001)

(untitled) - Mehiri, M.; Upert, G.; Tripathi, S.; Di Giorgio, A.; Condom, R.; Pandey, V. N.; Patino, N. (Oligonucleotides, 2008)

(untitled) - Shen, G.; Fang, H.; Song, Y.; Bielska, A. A.; Wang, Z.; Taylor, J.-S. A. (Bioconjugate Chem., 2009)

(untitled) - Shiraishi, T.; Nielsen, P. E. (Bioconjugate Chem., 2012)

(untitled) - Zhang, X.; Simmons, C. G.; Corey, D. R. (Bioorg. Med. Chem. Lett., 2001)

(untitled) - Herbert, B.-S.; Pitts, A. E.; Baker, S. I.; Hamilton, S. E.; Wright, W. E.; Shay, J. W.; Corey, D. R. (Proc. Natl. Acad. Sci. U. S. A., 1999)

(untitled) - Valentijn, A. R. P. M.; van der Marel, G. A.; Sliedregt, L. A. J. M.; van Berkel, T. J. C.; Biessen, E. A. L.; van Boom, J. H. (Tetrahedron, 1997)

(untitled) - Biessen, E. A. L.; Sliedregt-Bol, K.; 'T Hoen, P. A. C.; Prince, P.; Van der Bilt, E.; Valentijn, A. R. P. M.; Meeuwenoord, N. J.; Princen, H.; Bijsterbosch, M. K.; Van der Marel, G. A.; Van Boom, J. H.; Van Berkel, T. J. C. (Bioconjugate Chem., 2002)

(untitled) - van Rossenberg, S. M. W.; Sliedregt-Bol, K. M.; Prince, P.; van Berkel, T. J. C.; van Boom, J. H.; van der Marel, G. A.; Biessen, E. A. L. (Bioconjugate Chem., 2003)

(untitled) - Nair, J. K.; Willoughby, J. L. S.; Chan, A.; Charisse, K.; Alam, M. R.; Wang, Q.; Hoekstra, M.; Kandasamy, P.; Kel’in, A. V.; Milstein, S.; Taneja, N.; O’Shea, J.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Prakash, T. P.; Graham, M. J.; Yu, J.; Carty, R.; Low, A.; Chappell, A.; Schmidt, K.; Zhao, C.; Aghajan, M.; Murray, H. F.; Riney, S.; Booten, S. L.; et al. (Nucleic Acids Res., 2014)

(untitled) - Scott, L. J. (Drugs, 2020)

(untitled) - Bhingardeve, P.; Madhanagopal, B. R.; Naick, H.; Jain, P.; Manoharan, M.; Ganesh, K. (J. Org. Chem., 2020)

(untitled) - Petrus, A. K.; Fairchild, T. J.; Doyle, R. P. (Angew. Chem., Int. Ed., 2009)

(untitled) - Clardy, S. M.; Allis, D. G.; Fairchild, T. J.; Doyle, R. P. (Expert Opin. Drug Delivery, 2011)

(untitled) - Wierzba, A.; Wojciechowska, M.; Trylska, J.; Gryko, D. (Bioconjugate Chem., 2016)

(untitled) - Równicki, M.; Wojciechowska, M.; Wierzba, A. J.; Czarnecki, J.; Bartosik, D.; Gryko, D.; Trylska, J. (Sci. Rep., 2017)

(untitled) - Równicki, M.; Dąbrowska, Z.; Wojciechowska, M.; Wierzba, A. J.; Maximova, K.; Gryko, D.; Trylska, J. (ACS Omega, 2019)

(untitled) - Pieńko, T.; Czarnecki, J.; Równicki, M.; Wojciechowska, M.; Wierzba, A. J.; Gryko, D.; Bartosik, D.; Trylska, J. (Biophys. J., 2021)

(untitled) - Riguet, E.; Tripathi, S.; Chaubey, B.; Désiré, J.; Pandey, V. N.; Décout, J.-L. (J. Med. Chem., 2004)

(untitled) - Chaubey, B.; Tripathi, S.; Désiré, J.; Baussanne, I.; Décout, J.-L.; Pandey, V. N. (Oligonucleotides, 2007)

(untitled) - Das, I.; Désiré, J.; Manvar, D.; Baussanne, I.; Pandey, V. N.; Décout, J.-L. (J. Med. Chem., 2012)

(untitled) - Kesy, J.; Patil, K. M.; Kumar, S. R.; Shu, Z.; Yong, H. Y.; Zimmermann, L.; Ong, A. A. L.; Toh, D.-F. K.; Krishna, M. S.; Yang, L.; Decout, J.-L.; Luo, D.; et al. (Bioconjugate Chem., 2019)

(untitled) - Ong, A. A. L.; Tan, J.; Bhadra, M.; Dezanet, C.; Patil, K. M.; Chong, M. S.; Kierzek, R.; Decout, J.-L.; Roca, X.; Chen, G. (Molecules, 2019)

(untitled) - Ørum, H.; Nielsen, P. E.; Egholm, M.; Berg, R. H.; Buchardt, O.; Stanley, C. (Nucleic Acids Res., 1993)

(untitled) - Thiede, C.; Bayerdörffer, E.; Blasczyk, R.; Wittig, B.; Neubauer, A. (Nucleic Acids Res., 1996)

(untitled) - Nagai, Y.; Miyazawa, H.; Huqun; Tanaka, T.; Udagawa, K.; Kato, M.; Fukuyama, S.; Yokote, A.; Kobayashi, K.; Kanazawa, M.; Hagiwara, K. (Cancer Res., 2005)

(untitled) - Tanaka, T.; Nagai, Y.; Miyazawa, H.; Koyama, N.; Matsuoka, S.; Sutani, A.; Udagawa, K.; Murayama, Y.; Nagata, M.; Shimizu, Y.; Ikebuchi, K.; Kanazawa, M.; et al. (Cancer Sci., 2007)

(untitled) - Kim, H.-R.; Lee, S. Y.; Hyun, D.-S.; Lee, M. K.; Lee, H.-K.; Choi, C.-M.; Yang, S.-H.; Kim, Y.-C.; Lee, Y. C.; Kim, S. Y.; Jang, S. H.; Lee, J. C.; et al. (J. Exp. Clin. Cancer Res., 2013)

(untitled) - Song, J.; Hegge, J. W.; Mauk, M. G.; Chen, J.; Till, J. E.; Bhagwat, N.; Azink, L. T.; Peng, J.; Sen, M.; Mays, J.; Carpenter, E. L.; van der Oost, J.; et al. (Nucleic Acids Res., 2020)

(untitled) - Demidov, V. V. (Expert Rev. Mol. Diagn., 2001)

(untitled) - Bukanov, N. O.; Demidov, V. V.; Nielsen, P. E.; Frank-Kamenetskii, M. D. (Proc. Natl. Acad. Sci. U. S. A., 1998)

(untitled) - Kuhn, H.; Demidov, V. V.; Frank-Kamenetskii, M. D. (Nucleic Acids Res., 2002)

(untitled) - Smolina, I.; Lee, C.; Frank-Kamenetskii, M. (Appl. Environ. Microbiol., 2007)

(untitled) - Yaroslavsky, A. I.; Smolina, I. V. (Chem. Biol., 2013)

(untitled) - Xu, X.; Xing, S.; Xu, M.; Fu, P.; Gao, T.; Zhang, X.; Zhao, Y.; Zhao, C. (RSC Adv., 2019)

(untitled) - Lansdorp, P. M.; Verwoerd, N. P.; van de Rijke, F. M.; Dragowska, V.; Little, M.-T.; Dirks, R. W.; Raap, A. K.; Tanke, H. J. (Hum. Mol. Genet., 1996)

(untitled) - Vilaivan, T. (Beilstein J. Org. Chem., 2018)

(untitled) - Thisted, M. J. T.; Pluzek, K.-J.; Petersen, K. H.; Hyldigg-Nielsen, J.-J.; Godtfredsen, S. E. (Cell Visions, 1996)

(untitled) - Murakami, T.; Hagiwara, T.; Yamamoto, K.; Hattori, J.; Kasami, M.; Utsumi, M.; Kaneda, T. (J. Pathol., 2001)

(untitled) - Ortiz, E.; Estrada, G.; Lizardi, P. M. (Mol. Cell. Probes, 1998)

(untitled) - Armitage, B.; Ly, D.; Koch, T.; Frydenlund, H.; Ørum, H.; Schuster, G. B. (Biochemistry, 1998)

(untitled) - Seitz, O. (Angew. Chem., Int. Ed., 2000)

(untitled) - Kuhn, H.; Demidov, V. V.; Coull, J. M.; Fiandaca, M. J.; Gildea, B. D.; Frank-Kamenetskii, M. D. (J. Am. Chem. Soc., 2002)

(untitled) - Svanvik, N.; Ståhlberg, A.; Sehlstedt, U.; Sjöback, R.; Kubista, M. (Anal. Biochem., 2000)

(untitled) - Robertson, K. L.; Yu, L.; Armitage, B. A.; Lopez, A. J.; Peteanu, L. A. (Biochemistry, 2006)

(untitled) - Seitz, O.; Bergmann, F.; Heindl, D. (Angew. Chem., Int. Ed., 1999)

(untitled) - Köhler, O.; Jarikote, D. V.; Seitz, O. (ChemBioChem, 2005)

(untitled) - Socher, E.; Bethge, L.; Knoll, A.; Jungnick, N.; Herrmann, A.; Seitz, O. (Angew. Chem., Int. Ed., 2008)

(untitled) - Socher, E.; Knoll, A.; Seitz, O. (Org. Biomol. Chem., 2012)

(untitled) - Blanco, A. M.; Rausell, L.; Aguado, B.; Perez-Alonso, M.; Artero, R. (Nucleic Acids Res., 2009)

(untitled) - Koppitz, M.; Nielsen, P. E.; Orgel, L. E. (J. Am. Chem. Soc., 1998)

(untitled) - Pianowski, Z. L.; Winssinger, N. (Chem. Commun., 2007)

(untitled) - Pianowski, Z.; Gorska, K.; Oswald, L.; Merten, C. A.; Winssinger, N. (J. Am. Chem. Soc., 2009)

(untitled) - Kummer, S.; Knoll, A.; Socher, E.; Bethge, L.; Herrmann, A.; Seitz, O. (Bioconjugate Chem., 2012)

(untitled) - Peled, I.; Yavin, E. (ACS Omega, 2018)

(untitled) - Hashoul, D.; Shapira, R.; Falchenko, M.; Tepper, O.; Paviov, V.; Nissan, A.; Yavin, E. (Biosens. Bioelectron., 2019)

(untitled) - Stender, H.; Mollerup, T. A.; Lund, K.; Petersen, K. H.; Hongmanee, P.; Godtfredsen, S. E. (Int. J. Tuberc. Lung Dis., 1999)

(untitled) - Oliveira, K.; Procop, G. W.; Wilson, D.; Coull, J.; Stender, H. (J. Clin. Microbiol., 2002)

(untitled) - Rigby, S.; Procop, G. W.; Haase, G.; Wilson, D.; Hall, G.; Kurtzman, C.; Oliveira, K.; Von Oy, S.; Hyldig-Nielsen, J. J.; Coull, J.; Stender, H. (J. Clin. Microbiol., 2002)

(untitled) - Xi, C.; Balberg, M.; Boppart, S. A.; Raskin, L. (Appl. Environ. Microbiol., 2003)

(untitled) - Wilson, D. A.; Joyce, M. J.; Hall, L. S.; Reller, L. B.; Roberts, G. D.; Hall, G. S.; Alexander, B. D.; Procop, G. W. (J. Clin. Microbiol., 2005)

(untitled) - Ly, T.; Gulia, J.; Pyrgos, V.; Waga, M.; Shoham, S. (Ther. Clin. Risk Manage., 2008)

(untitled) - Cerqueira, L.; Fernandes, R. M.; Ferreira, R. M.; Carneiro, F.; Dinis-Ribeiro, M.; Figueiredo, C.; Keevil, C. W.; Azevedo, N. F.; Vieira, M. J. (BMC Microbiol., 2011)

(untitled) - Abdelhamed, A. M.; Zhang, S. X.; Watkins, T.; Morgan, M. A.; Wu, F.; Buckner, R. J.; Fuller, D. D.; Davis, T. E.; Salimnia, H.; Fairfax, M. R.; Lephart, P. R.; Poulter, M. D.; et al. (J. Clin. Microbiol., 2015)

(untitled) - Mach, K. E.; Kaushik, A. M.; Hsieh, K.; Wong, P. K.; Wang, T.-H.; Liao, J. C. (Analyst, 2019)

(untitled) - Su, X.; Teh, H. F.; Lieu, X.; Gao, Z. (Anal. Chem. (Washington, DC, U. S.), 2007)

(untitled) - Zhang, G.-J.; Chua, J. H.; Chee, R.-E.; Agarwal, A.; Wong, S. M. (Biosens. Bioelectron., 2009)

(untitled) - Sadhu, K. K.; Winssinger, N. (Chem. – Eur. J., 2013)

(untitled) - Ryoo, S.-R.; Lee, J.; Yeo, J.; Na, H.-K.; Kim, Y.-K.; Jang, H.; Lee, J. H.; Han, S. W.; Lee, Y.; Kim, V. N.; Min, D.-H. (ACS Nano, 2013)

(untitled) - Kotikam, V.; Fernandes, M.; Kumar, V. A. (Phys. Chem. Chem. Phys., 2012)

(untitled) - Hong, C.; Baek, A.; Hah, S. S.; Jung, W.; Kim, D.-E. (Anal. Chem. (Washington, DC, U. S.), 2016)

(untitled) - Metcalf, G. A. D.; Shibakawa, A.; Patel, H.; Sita-Lumsden, A.; Zivi, A.; Rama, N.; Bevan, C. L.; Ladame, S. (Anal. Chem. (Washington, DC, U. S.), 2016)

(untitled) - Pavagada, S.; Channon, R. B.; Chang, J. Y. H.; Kim, S. H.; MacIntyre, D.; Bennett, P. R.; Terzidou, V.; Ladame, S. (Chem. Commun., 2019)

(untitled) - Sayers, J.; Payne, R. J.; Winssinger, N. (Chem. Sci., 2018)

(untitled) - Thurley, S.; Röglin, L.; Seitz, O. (J. Am. Chem. Soc., 2007)

(untitled) - Oh, K. J.; Cash, K. J.; Lubin, A. A.; Plaxco, K. W. (Chem. Commun., 2007)

(untitled) - Dhar, A.; Ahmed, I.; Mallick, S.; Roy, S. (ChemBioChem, 2020)

(untitled) - Nielsen, P. E.; Egholm, M.; Buchardt, O. (Gene, 1994)

(untitled) - Knudsen, H.; Nielsen, P. E. (Nucleic Acids Res., 1996)

(untitled) - Doyle, D. F.; Braasch, D. A.; Janowski, B. A.; Corey, D. R. (Biochemistry, 2001)

(untitled) - Economos, N. G.; Oyaghire, S.; Quijano, E.; Ricciardi, A. S.; Saltzman, W. M.; Glazer, P. M. (Molecules, 2020)

(untitled) - Hyrup, B.; Nielsen, P. E. (Bioorg. Med. Chem., 1996)

(untitled) - Demidov, V. V.; Potaman, V. N.; Frank-Kamenetskil, M. D.; Egholm, M.; Buchard, O.; Sönnichsen, S. H.; Nielsen, P. E. (Biochem. Pharmacol., 1994)

(untitled) - Uhlmann, E.; Peyman, A.; Breipohl, G.; Will, D. W. (Angew. Chem., Int. Ed., 1998)

(untitled) - Kaushik, N.; Basu, A.; Palumbo, P.; Myers, R. L.; Pandey, V. N. (J. Virol., 2002)

(untitled) - Kolevzon, N.; Nasereddin, A.; Naik, S.; Yavin, E.; Dzikowski, R. (PLoS One, 2014)

(untitled) - Yin, H.; Lu, Q.; Wood, M. (Mol. Ther., 2008)

(untitled) - Yin, H.; Betts, C.; Saleh, A. F.; Ivanova, G. D.; Lee, H.; Seow, Y.; Kim, D.; Gait, M. J.; Wood, M. J. A. (Mol. Ther., 2010)

(untitled) - Gao, X.; Shen, X.; Dong, X.; Ran, N.; Han, G.; Cao, L.; Gu, B.; Yin, H. (Mol. Ther.–Nucleic Acids, 2015)

(untitled) - Brolin, C.; Lim, E. W. K.; Grizot, S.; Olsen, C. H.; Yavari, N.; Krag, T. O.; Nielsen, P. E. (Nucleic Acid Ther., 2021)

(untitled) - Kayali, R.; Bury, F.; Ballard, M.; Bertoni, C. (Hum. Mol. Genet., 2010)

(untitled) - Nik-Ahd, F.; Bertoni, C. (Stem Cells (Durham, NC, U. S.), 2014)

(untitled) - Bahal, R.; Ali McNeer, N.; Quijano, E.; Liu, Y.; Sulkowski, P.; Turchick, A.; Lu, Y.-C.; Bhunia, D. C.; Manna, A.; Greiner, D. L.; Brehm, M. A.; Cheng, C. J.; et al. (Nat. Commun., 2016)

(untitled) - Boffa, L. C.; Cutrona, G.; Cilli, M.; Mariani, M. R.; Matis, S.; Pastorino, M.; Damonte, G.; Millo, E.; Roncella, S.; Ferrarini, M. (Oligonucleotides, 2005)

(untitled) - Boffa, L. C.; Cutrona, G.; Cilli, M.; Matis, S.; Damonte, G.; Mariani, M. R.; Millo, E.; Moroni, M.; Roncella, S.; Fedeli, F.; Ferrarini, M. (Cancer Gene Ther., 2007)

(untitled) - Alagpulinsa, D. A.; Yaccoby, S.; Ayyadevara, S.; Shmookler Reis, R. J. (Cancer Biol. Ther., 2015)

(untitled) - Babar, I. A.; Cheng, C. J.; Booth, C. J.; Liang, X.; Weidhaas, J. B.; Saltzman, W. M.; Slack, F. J. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Malik, S.; Lim, J.; Slack, F. J.; Braddock, D. T.; Bahal, R. (J. Controlled Release, 2020)

(untitled) - Gupta, A.; Quijano, E.; Liu, Y.; Bahal, R.; Scanlon, S. E.; Song, E.; Hsieh, W.-C.; Braddock, D. E.; Ly, D. H.; Saltzman, W. M.; Glazer, P. M. (Mol. Ther.–Nucleic Acids, 2017)

(untitled) - Kim, K.; Kim, H. H.; Lee, C.-H.; Kim, S.; Cheon, G. J.; Kang, K. W.; Chung, J.-K.; Youn, H. (Biochem. Biophys. Res. Commun., 2020)

(untitled) - Tan, X.-X.; Actor, J. K.; Chen, Y. (Antimicrob. Agents Chemother., 2005)

(untitled) - Abushahba, M. F. N.; Mohammad, H.; Thangamani, S.; Hussein, A. A. A.; Seleem, M. N. (Sci. Rep., 2016)

(untitled) - Feng, S.; Holland, E. C. (Nature, 1988)

(untitled) - Chaubey, B.; Tripathi, S.; Ganguly, S.; Harris, D.; Casale, R. A.; Pandey, V. N. (Virology, 2005)

(untitled) - Amit-Avraham, I.; Pozner, G.; Eshar, S.; Fastman, Y.; Kolevzon, N.; Yavin, E.; Dzikowski, R. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Faruqi, A. F.; Egholm, M.; Glazer, P. M. (Proc. Natl. Acad. Sci. U. S. A., 1998)

(untitled) - Chin, J. Y.; Kuan, J. Y.; Lonkar, P. S.; Krause, D. S.; Seidman, M. M.; Peterson, K. R.; Nielsen, P. E.; Kole, R.; Glazer, P. M. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - McNeer, N. A.; Chin, J. Y.; Schleifman, E. B.; Fields, R. J.; Glazer, P. M.; Saltzman, W. M. (Mol. Ther., 2011)

Methods in Molecular Biology - Oyaghire, S. N.; Quijano, E.; Piotrowski-Daspit, A. S.; Saltzman, W. M.; Glazer, P. M. (Poly(Lactic-co-Glycolic Acid) Nanoparticle Delivery of Peptide Nucleic Acids In Vivo, 2020)

(untitled) - Xu, P.; Tong, Y.; Liu, X.-z.; Wang, T.-t.; Cheng, L.; Wang, B.-y.; Lv, X.; Huang, Y.; Liu, D.-p. (Sci. Rep., 2015)

(untitled) - Song, B.; Fan, Y.; He, W.; Zhu, D.; Niu, X.; Wang, D.; Ou, Z.; Luo, M.; Sun, X. (Stem Cells Dev., 2015)

(untitled) - Li, Z.; Rana, T. M. (Nat. Rev. Drug Discovery, 2014)

(untitled) - Cha, W.; Fan, R.; Miao, Y.; Zhou, Y.; Qin, C.; Shan, X.; Wan, X.; Cui, T. (Med. Chem. Commun., 2018)

(untitled) - Wojciechowska, M.; Równicki, M.; Mieczkowski, A.; Miszkiewicz, J.; Trylska, J. (Molecules, 2020)

(untitled) - Good, L.; Sandberg, R.; Larsson, O.; Nielsen, P. E.; Wahlestedt, C. (Microbiology (London, U. K.), 2000)

(untitled) - Gambari, R. (Expert Opin. Ther. Pat., 2014)